Performance of Local Government Units basis for strengthening barangay function and responsibilities - Sy, Maria Blanca S. (2016)
The study described the level of performance of the Local Government Units (LGUs) in the localities bordering the province of Zamboanga del Norte. Selected barangays were rated by the officials and residents as to Governance, Barangays Fiscal Administration, Development Planning, Barangay Legislation, Barangay Basic Services and Facilities and Compliance to Directives using standard questionnaires by the Department of Interior and Local Government Unit (DILG). The findings revealed that Governance, Barangay Fiscal Administration, Development Planning, Barangay Legislation, Barangay Basic Services and Facilities and Compliance to Directives were satisfactorily performed. This necessitate that the barangay officials should look into the six areas for barangay development and initiate programs in order to augment the livelihood source, income, economy and the constituent’s quality of life. Importantly barangays officials should encourage the community people to develop entrepreneurial endeavors as a way of augmenting barangay income and economy.
Keywords: Mindanao studies; Local Government Units; Barangays